Photo Catalytic Removal of Sodium Dodecyl Sulfate From Aquatic Solutions With Prepared ZnO Nanocrystals and UV Irradiation - Mohammad Taghi Samadi; Mir Saeid Sayed Dorraji; Zolykha Atashi; Ali Reza Rahmani (Hamadan University of Medical Sciences, 2014)
In this study, ZnO Nano catalyst has been synthesized and examined as photo catalyst for UV-induced removal of Sodium Dodecyl Sulfate (SDS) from aquatic solutions. This anionic surfactant was selected based upon its toxicity, wide use in industrial laundry and as a primary pollutant in municipal waste water systems.This study aimed to investigate removal of surfactant, SDS, in a batch photo catalytic reactor under various operating conditions including ZnO suspension concentration, initial surfactant concentration and initial pH of solution to find out the desired condition for removal of surfactant. ZnO Nano crystals were synthesized using the precipitation method and ZnSO4.7H2O was used as the starting material and NaOH as precipitant. The removal of SDS reactions by UV/ZnO process was performed into a batch photo reactor. In addition, various operating conditions including ZnO suspension concentration, initial surfactant concentration and initial pH of solution were investigated. In total, 98% of surfactant was removed at 40 minute and removal efficiency of SDS increased with increasing pH up to nine and after that with increase in pH, efficiency decreased. Possible roles of inorganic oxidant on the reaction were discussed. The removal of SDS follows pseudo-first order kinetics. Based on the results of this study, ZnO-UV photo catalytic process can be used as an efficient method for further study in detergents removal.